4. RESEARCH ON THE APPLICATION OF PERCUTANEOUS CARDIOVASCULAR INTERVENTION METHOD IN TREATMENT OF CONGENITAL HEART DISEASE WITH LEFT - RIGHT SCHEDULE AT THANH HOA CHILDREN'S HOSPITAL IN 2018-2019 (Vietnam Journal of Community Medicine, 2025)
disease with left - right shunt at Thanh Hoa Pediatric Hospital in 2018-2019.Research methods: Describe the prospective study with comparison before and after intervention in patients with congenital heart disease with left - right shunt treated with percutaneous intervention at Thanh Hoa Pediatric Hospital from June 2018 to April 2020.Results: There were 56 patients (21 men and 35 women), aged from 3.4 to 195.7 months, including: 12 patients with ventricular septal defect, 10 patients with atrial septal defect, 33 patients with patent ductus arteriosus and 1 patient with left aorta left window. The average ostium size on echocardiography was 4.7 mm. Common clinical symptoms are: difficulty breathing (6.8%), chest deformity (14.3%), slow weight gain (50%), heart murmur (85.7%). 100% success rate, no complications or death. The residual shunt rate after 24-hour intervention is 26.8%, after 1 month is 8.9% and after 3 months is 0%.Conclusions: Percutaneous cardiovascular intervention to treat congenital heart diseases with left - right shunt is a new, feasible, safe technique with a high success rate (100%).
Keywords: Percutaneous cardiovascular intervention; congenital heart; left - right shunt